GROUND-BASED STATION NETWORK IN ARCTIC AND SUBARCTIC EURASIA: AN OVERVIEW - Pavel Alekseychik; Hanna K. Lappalainen; Tuukka Petäjä; Nina Zaitseva; Martin Heimann; Tuomas Laurila; Heikki Lihavainen; Eija Asmi; Mikhail Arshinov; Vladimir Shevchenko; Alexander Makshtas; Sergey Dubtsov; et al. (Geography, Environment, Sustainability)
The international Pan-Eurasian Experiment (PEEX) program addresses the full spectrum of problems related to climate change in Eurasian Northern latitudes. All PEEX activities rely on the bulk of high-quality observational data provided by the ground and marine stations, remote sensing and satellite tools. So far, no coordinated station network has ever existed in Eurasia, moreover, the current scope of relevant research remains largely unknown as no prior assessment has been done to date. This paper makes the first attempt to overview the existing ground station pool in the Arctic-Boreal region with the focus on Russia. The  geographical, climatic and ecosystem representativeness of the current stations is discussed, the gaps are identified and tentative station network developments are proposed.